Security Concerns of Generative AI on Social Media - Gurwinder Singh; Ramanpreet Kaur; Khushboo Bharti (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rise of generative AI technologies has transformed the landscape of social media by enabling the creation of highly realistic and persuasive content. While these advancements offer exciting possibilities for creativity, communication, and engagement, they also introduce significant security concerns. The ability of generative AI to produce deepfakes, misinformation, and other manipulative content poses risks to personal privacy, political stability, and societal trust. This paper explores the security implications of generative AI on social media platforms, examining the challenges of identifying and mitigating AI-generated threats, the role of platform governance in addressing these issues, and the potential for malicious actors to exploit AI for cyberattacks. Additionally, we discuss the ethical considerations surrounding AI-generated content, privacy violations, and the responsibility of tech companies to safeguard users. Finally, we propose strategies for enhancing AI detection systems, fostering public awareness, and promoting the development of responsible AI policies to ensure a secure and trustworthy digital environment.